Inhibition of microRNA-155 Alleviates Cognitive Impairment in Alzheimer’s Disease and Involvement of Neuroinflammation - Liu, Dandan; Zhao, Dandan; Zhao, Yingkai; Wang, Yan; Zhao, Yong; Wen, Chengfei (Current Alzheimer Research, 2019)
Background: Neuroinflammation has important effects on cognitive functions in the pathophysiological process of Alzheimer’s Disease (AD). In the current report, we determined the effects of microRNA-155 (miR-155) on the levels of IL-1β, IL-6 and TNF-α, and their respective receptors in the hippocampus using a rat model of AD. Methods: Real-time RT-PCR, ELISA and western blot analysis were used to examine the miR-155, PICs and PIC receptors. The Morris water maze and spatial working memory tests were used to assess cognitive functions. Results: miR-155 was increased in the hippocampus of AD rats, accompanied by amplification of IL-1β, IL-6 and TNF-α. Intracerebroventricular infusion of miR-155 inhibitor, but not its scramble attenuated the increases of IL-1β, IL-6 and TNF-α and upregulation of their receptors. MiR-155 inhibitor also attenuated upregulation of apoptotic Caspase-3 in the hippocampus of AD rats. Notably, inhibition of miR- 155 or PIC receptors largely recovered the impaired learning performance in AD rat. Conclusion: We showed the critical role of miR-155 in regulating the memory impairment in AD rats likely via engagement of neuroinflammatory mechanisms, suggesting that miR-155 and its signaling molecules may present prospects in preventing and/or improving the development of the impaired cognitive functions in AD.
Keywords: pro-inflammatory cytokines